2013
DOI: 10.1200/jco.2012.45.2722
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia in the Age of Obesity: Skeletal Muscle Depletion Is a Powerful Prognostic Factor, Independent of Body Mass Index

Abstract: CT images reveal otherwise occult muscle depletion. Patients with cancer who are cachexic by the conventional criterion (involuntary weight loss) and by two additional criteria (muscle depletion and low muscle attenuation) share a poor prognosis, regardless of overall body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
2,421
23
46

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 2,170 publications
(2,563 citation statements)
references
References 28 publications
73
2,421
23
46
Order By: Relevance
“…In addition, we found that the changes in SMM are not reflected by the observed changes in body weight. This is in agreement with previous studies that state that body weight and BMI are not appropriate tools to understand the effect of systemic treatment on body composition 4, 6…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, we found that the changes in SMM are not reflected by the observed changes in body weight. This is in agreement with previous studies that state that body weight and BMI are not appropriate tools to understand the effect of systemic treatment on body composition 4, 6…”
Section: Discussionsupporting
confidence: 93%
“…BMI, body mass index; CAPOX‐B, capecitabine + oxaliplatin + bevacizumab; SD, standard deviation; WHO, World Health Organization.aSarcopenia for males was defined as skeletal muscle index of <43 cm 2 /m 2 if BMI <25 kg/m 2 or <53 cm 2 /m 2 for males if BMI ≥25 kg/m 2 , and sarcopenia for females was skeletal muscle index <41 cm 2 /m 2 for any BMI 6b

Sarcopenic obesity was defined as being sarcopenic and BMI >30 kg/m 2 .

…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations